Edukasi Pelestarian Lingkungan Melalui Pengenalan Kosakata dan Kalimat Bahasa Inggris Bertema Lingkungan pada Anak Usia Dini di Desa Tanggap Bencana: - - Vania Madeline Sayuna; Euis Zian Safitri; Santi Farmasari; Amliaya Putri; Nur Asia; I Gde Kusmananda Satya Narayana; Muliati (Jurnal Pengabdian Magister Pendidikan IPA, 2022)
This community service was conducted in Gelangsar Village, West Lombok. Gelangsar Village is one of disaster-prepared villages in West Lombok District of West Nusa Tenggara Province. The village is also appointed as one of tourism villages in West Lombok. The community service was aimed at educating young children about the importance of preserving their local environment to prevent detrimental disasters. The education about environment was integrated in the English informal classes by introducing English vocabularies and sentences related to environment issues. The English classes were impossible to be conducted without the supports and assistances from the head of the village and the children’s parents. The supports and assistances provided for theEnglish classes were evidences of the villagers’ awareness of the importance of educating the children about the disaster risks in their village and educating them about some strategies to prevent disasters through English.